Solar Wind Sputtering Rates of Small Bodies and Ion Mass Spectrometry Detection of Secondary Ions. Issue 10 (14th October 2017) - Schaible, M. J.; Dukes, C. A.; Hutcherson, A. C.; Lee, P.; Collier, M. R.; Johnson, R. E.
Abstract: Solar wind interactions with the surfaces of asteroids and small moons eject atoms and molecules from the uppermost several nanometers of regolith grains through a process called sputtering. A small fraction of the sputtered species, called secondary ions, leave the surface in an ionized state, and these are diagnostic of the surface composition. Detection of secondary ions using ion mass spectrometry (IMS) provides a powerful method of analysis due to low backgrounds and high instrument sensitivities. However, the sputtered secondary ion yield and the atomic composition of the surface are not 1‐to‐1 correlated. Thus, relative yield fractions based on experimental measurements are needed to convert measured spectra to surface composition. Here available experimental results are combined with computationally derived solar wind sputtering yields to estimate secondary ion fluxes from asteroid‐sized bodies in the solar system. The Monte Carlo simulation code SDTrimSP is used to estimate the total sputtering yield due to solar wind ion bombardment for a diverse suite of meteorite and lunar soil compositions. Experimentally measured relative secondary ion yields are analyzed to determine the abundance of refractory species (Mg +, Al +, Ca +, and Fe + ) relative to Si +, and it is shown that relative abundances indicate whether a body is primitive or has undergone significant geologic reprocessing. Finally, estimates of the sputtered secondary ion fluxes are used to determine the IMS sensitivity required to adequately resolve major element ratios for nominal orbital geometries. Plain Language Summary: Determining the precise atomic composition of airless bodies in the solar system can only be carried out by returning samples to Earth, landing on the surface, or sampling the atmosphere. Solar wind plasma ejects atoms and ions from the surfaces of airless bodies, and these ions can be detected with high sensitivity using ion mass spectrometry. Using combined experimental and computational results, we present a model that can be used to estimate the rate at which ions are ejected from the surfaces of airless bodies and show that such ejected ions can be easily detected using mass spectrometry techniques. Furthermore, it is shown that analysis of the relative amounts of sputtered refractory species such as Fe, Si, and Mg can be used to constrain the geologic history of such bodies. We conclude that including an ion mass spectrometer on a spacecraft mission will allow the composition of the uppermost surface to be determined and will also provide information on the likely environment in which the body formed. Such information could prove immensely valuable in determining the history of bodies in our solar system and the availability of resources in our solar neighborhood. Key Points: Solar wind sputtering of airless bodies ejects abundant secondary ions into the exosphere surrounding the body Sputtered secondary ion fluxes can be easily detected using available ion mass spectrometers Analysis of the relative abundance of sputtered secondary ions can be used to constrain the geologic history of small bodies